Mens en Omgeving (4) : Het Konstante Streven. - De Beyerd, Breda (Breda : De Beyerd Breda, 1983)
van Gogh, Vincent ; Mackmurdo, Arthur M. ; Wils, Jan ; d'Urbino, De Pas Lomazzi ; Panton, Verner ; Aarnio, Eero ; Giezen, Krijn ; Breuer, Marcel ; Albini ; Sotsass, Ettore ; Garner, Philip ; Gragg, Tony ; Wilhite, Bob ; Gaudi, Antonio
Mens en Omgeving (4) : Het Konstante Streven, De Beyerd, Breda, 31.12.1983 tot en met 12.2.1983
boek